PELATIHAN KEWIRAUSAHAAN IBU-IBU PKK DI KECAMATAN PURWOKERTO TIMUR DENGAN MEMANFAATKAN MEDIA SOSIAL - Muh Sofi'i; wika purbasari; NOVITA SETIANTI; joko purnomo; Sunaryono Sunaryono (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2022)
Along with the development of the times, human needs for information and the use of technology (internet) is growing rapidly. By using the internet, especially social networks, people of all ages, gender, social class, economy and culture can know the various developments that occur in their environment and can interact with each other without being limited by space and time. Currently, Instagram has become one of the most widespread social networking categories used by most people in Indonesia to introduce and promote their products. Instagram is believed to be not only beneficial for online shop, retailer, restaurant, travel company, and e-commerce, but also one of the most effective tools in building a business brand. In fact, Instagram is also not only in demand by men and women who are young entrepreneurs, but also housewives who have passion in developing business from home (home business). The activity (Pengabdian Masyarakat) that was held on monday, april 26, 2021 is basically done to socialize the use of Instagram as social networking among PKK (Pembinaan Kesejahteraan Keluarga) East Purwokerto District, Banyumas, Central Java. Training is done by using classical method for 1.5 hours in the form of Instagram account creation, delivery of core material by expert speakers, and sharing experiences to motivate mothers to become mompreneur.